REALIZING FINANCIAL INCLUSION IN THE MEDAN AREA SUBDISTRICT: THE ROLE OF FINANCIAL WELL-BEING, FINANCIAL LITERACY, AND INCOME WITHIN A SOCIO-CULTURAL FRAMEWORK - Sri Fitri Wahyuni; Raudatul Jannah (RADJA PUBLIKA, 2025)
The objective of this study is to examine and analyze the influence of financial well-being, financial literacy, and income on financial inclusion, as well as to assess the moderating role of socio-cultural factors in these relationships. A quantitative research approach was employed using a survey method. The study population consisted of individuals of productive age residing in the Medan Area Subdistrict. A purposive sample of 100 respondents was drawn from two urban villages with distinct socio-economic characteristics. Data were collected through a structured questionnaire and analyzed using SmartPLS 4.0 software. The findings reveal that financial well-being, financial literacy, and income significantly influence financial inclusion. Socio-cultural factors also exert a direct and significant impact on financial inclusion. However, when tested as a moderating variable, socio-cultural factors were found to significantly moderate only the relationship between financial well-being and financial inclusion. In contrast, no significant moderating effects were observed in the relationships between financial literacy and income with financial inclusion. These results highlight that economic participation in formal financial systems is shaped not only by individual financial conditions but also by the cultural values embedded within the community.